Money Laundering and International Efforts to Fight It - Scott, David (World Bank, Washington, DC, 2012)
According to one estimate, US$300 billion to US$500 billion in proceeds from serious crime is laundered each year. Left unchecked, money laundering could criminalize the financial system and undermine development efforts in emerging markets. The author reviews efforts by international bodies to fight it.